The influence of nano kaolin clay as alternative binder on the penetration properties - Abdul Hassan, Norhidayah; Ismail, Che Ros; Al-Saffar, Zaid Hazim; Putra Jaya, Ramadhansyah; Masri, Khairil Azman; Muzamir, H; Wan Azahar, Wan Nur Aifa (IOP Publishing, 2021)
In the last decade or so, nanomaterials have emerged as the potential solution to greatly enhance the properties of binder with the purpose of improving the performance of asphalt mixture. Due to that, this study evaluates the influence of nano kaolin clay as alternative binder on the penetration properties. The penetration test, penetration index and penetration-viscosity number were conducted in modifying the binder with the percentage of NKC are 0, 3, 5, 7 and 9%, accordingly. The test results showed that the penetration values of modified binder slightly decreased when compared to the controlled binder. On the other hand, the PI and PVN values significantly increase with the NKC content increased.